Mereduksi Perilaku Misbehave Siswa Melalui Sosialisasi Manajemen Kelas Ramah Anak Di Ponpers Mutiara Qur’an Boarding School Bengkalis - Aisyah Nuramini; Ismatul Maula (LPPM-IAI Hidayatullah Batam, 2026)
Deviant behavior is behavior that does not conform to norms and is carried out by students. This behavior initially develops in the classroom. Preventing deviant behavior is a must for teachers. This community service aims to broaden teachers' understanding and skills in reducing student deviant behavior through child-friendly classroom management. The method used is a participatory education-based educational socialization approach. The results of the study indicate an increase in teachers' understanding of student deviant behavior in the classroom and the strategies that can be used. The emergence of student problems is a sign that students are growing, seeking direction, and need guidance. Teachers, as adults, have an obligation to accompany students' learning process amidst increasingly dynamic conditions. Child-friendly classroom management ensures that students' rights are fulfilled, guaranteed, and protected in obtaining education, and teachers can raise students' awareness about learning in school.